Mutation detection on isotype-1 Î² tubulin genes of Haemonchus contortus resistant strain to benzimidazole using single strand conformation polymorphism - Haryuningtyas, Dyah (Indonesian Journal of Animal and Veterinary Sciences, 2005)
Evidence of anthelmintic resistance of Haemonchus contortus to benzimidazole groups based on Larval development assay (LDA) and Fecal egg count reduction test (FECRT) test has been reported in some areas in Indonesia. Studies on sheep parasite H. contortus have shown that resistance to benzimidazole drugs is correlated with selection for individuals in the population possesing a spesific isotype-1 Î² tubulin gene. The aim of this study was to determine mutation on central part of isotype-1 Î² tubulin gene of benzimidazole resistant strain H. contortus using Single Strand Conformation Polymorphism (SSCP). H. contortus worms were isolated from four sheep from two government farms that resistance to benzimidazole have been occurred (SPTD Trijaya, Kuningan, West Java and UPTD Pelayanan Kesehatan Hewan, Bantul, Yogyakarta) and one sheep that susceptible from Cicurug, Bogor, West Java as a kontrol. Resistance status to benzimidazole was reexamined individually with LDA and FECRT before sheep slaughtered. DNA was extracted from female H. contortus worms. A fragment of 520 bp isotype- 1 Î² tubulin gene was amplified using Polymerase chain reaction (PCR) and then analyze using SSCP. The results showed that there were polymorphism in isotype-1 Î² tubulin gene among H. contortus susceptible (Cicurug, Bogor, Jawa Barat) and two H. contortus resistant strains from SPTD Trijaya, Kuningan, West Java and UPTD Pelayanan Kesehatan Hewan, Bantul, Yogyakarta. Mutation occurred in the different nucleotide of the two resistant strain. Â  Â  Key Words: Haemonchus contortus, Benzimidazole, Isotype-1 Î² tubulin gene, SSCP